Synthetic Curcumin Derivative DK1 Possessed G2/M Arrest and Induced Apoptosis Through Accumulation of Intracellular ROS in MCF-7 Breast Cancer Cells - Norlaily, Mohd Ali; Swee, Keong Yeap; Nadiah, Abu; Kian, Lam Lim; Huynh, Ky; Ahmad Zaim, Mat Pauzi; Wan, Yong Ho; Sheau, Wei Tan; Han, Kiat Alan-Ong; Seema, Zareen; Noorjahan Banu, Alitheen; Akhtar, Muhammad Nadeem (BioMed Central, 2017)
Curcumin is a lead compound of the rhizomes of Curcuma longa and possess a broad range of pharmacological activities. Chemically, curcumin is 1,3-dicarbonyl class of compound, which exhibits keto-enol tautomerism. Despite of its strong biological properties, curcumin has yet been recommended as a therapeutic agent because of its poor bioavailability. A curcumin derivative (Z)-3-hydroxy-1-(2-hydroxyphenyl)-3-phenylprop-2-en-1-one (DK1) was synthesized and its cytotoxicity was tested on breast cancer cell MCF-7 and normal cell MCF-10A using MTT assay. Meanwhile, cell cycle regulation and apoptosis on MCF-7 cell were evaluated using flow cytometry. Regulation of cell cycle and apoptosis related genes expression was investigated by quantitative real time polymerase chain reaction (qRT-PCR), western blot and caspases activity analyses. Activation of oxidative stress on MCF-7 were evaluated by measuring ROS and GSH levels.